ALTERED POSTURAL CONTROL STRATEGIES IN PEOPLE WITH CHRONIC LOW BACK PAIN: AN OVERACTIVE LATISSIMUS DORSI? - FINTA, Regina; KATONA, Peter; NAGY, Edit (Romanian Journal of Physical Therapy / Revista Romana de Kinetoterapie, 2021)
Purpose: The aim of the research is to examine the possible alterations in the functioning of muscles in chronic low back pain (LBP). Method: In this prospective study 35 people were selected into LBP and control (C) groups after they had completed the Chronic Pain Grade Scale. 12 muscles were measured with surface electromyography during a functional balance task. Results: In rate of muscle recruitment significant increase was found, the LBP group recruited latissimus dorsi muscle (LD) to implement the movement task. During the functional task, the agonist muscles in the LBP group were not recruited as much as in the C group; however, the antagonist muscles were activated more frequently in the LBP group. The activity level of the agonist and stabilizer muscles was higher in the LBP group, whereas the activity level of antagonists was rather lower in the LBP group than in the C one. Conclusion: People with LBP recruit more antagonist muscles but use these muscles at a lower activity level. In the recruitment pattern, the role of LD seems to be dominant. Clinicians should consider the role of LD in LBP during the rehabilitation process. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.